Night song ebook A novel. - Williams, John A. (Open Road Media, 2016)
Inspired by the life of Charlie “Bird” Parker, this poignant, provocative, and stylistically brilliant tale paints a vivid picture of the New York City jazz scene In Greenwich Village, jazz is king, enticing hip young crowds with its seductive and vibrant rhythms.   Jazz is also the lifeblood pumping through the veins of Richie “Eagle” Stokes, a saxophonist blessed with an otherworldly talent but cursed by cravings for women, fame, and heroin. To ex–college professor David Hillary, musicians like Stokes are gods possessed with the uncanny ability to turn a private inner world inside out and make everything else irrelevant. And for ex-preacher Keel Robinson, Hillary’s unlikely savior, the bewitching music serves as a bridge across racial boundaries as he embarks on a forbidden and dangerous love affair.   Considered one of the finest novelists of a generation that included James Baldwin, Ralph Ellison, and Richard Wright, author John A. Williams follows a diverse cast of all-too-human characters through nighttime New York City in this incendiary and unforgettable novel.